PENGARUH PROPORSI DEWAN KOMISARIS INDEPENDEN, LEVERAGE, UKURAN PERUSAHAAN DAN FREE CASH FLOW TERHADAP MANAJEMEN LABA (Studi pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia periode 2014-2017) - Maulidina, Yulina; Kristanti, Farida Titik (Aksara Public, 2018)
This study aims to determine the simultaneous and partial effects of the proportion of independent commissioners, leverage, company size, and free cash flow on earnings management. The population in this study are the food and beverage sub-sector companies listed on the Indonesia Stock Exchange 2014-2017. The sample selection technique uses a purposive sampling technique so that the companies that become the study sample are 14 companies out of a population of 18 companies. Data analysis used is panel data regression analysis using software eviews 9. The results of this study reveal that there is a simultaneous influence between the independent and dependent variables. Whereas for the partial effect only the proportion of board of commissioners and leverage has an effect on earnings management, while for firm size variables and free cash flow does not affect earnings management. In this study the proportion of independent board of commissioners has a negative and significant influence and leverage has a positive and significant influence on earnings management, meaning in investment decision making that can be considered or focused by looking at the number of independent commissioners in the company to oversee the performance of company managers. besides that investors must be careful with companies that have a high level of leverage ratio because it can be estimated that their management practices earnings management.